Association study of the polymorphism of the BoLA DQA1 class II gene with resistence/susceptibility to mastitis in Holstein cattle from the province of La Pampa (Veterinary Science, 2022)
Mastitis is a frecuently disease of dairy cattle that leads to a decrease in production and an increase in health costs. This disease can be evaluatedthrough the number of white blood cells per milliliter of milk, which is known as somatic cell count (CCS). Alleles of Bovine LeukocyteAntigen (BoLA) genes were associated with resistance and susceptibility to infectious diseases. The objective of this work was to study thepolymorphism of the class II molecules of BoLA-DQA1 and their association with resistance/susceptibility to mastitis measured through theCCS in milk in Holstein cattle from the province of La Pampa. The population was divided into: 1) case group with high CCS and presenceof mastitis (≥ 250,000 cel/ml, susceptible) and 2) control group with low CCS (
Keywords: BoLA-DQA1, resistance, susceptibility, mastitis, somatic cell